Racial discrimination, the superwoman schema, and allostatic load: exploring an integrative stress-coping model among African American women - Allen, Amani M. (Ann N Y Acad Sci, 2019)
Racial discrimination has been linked to allostatic load (i.e., cumulative biological stress) among African American women. Coping is a central component of the stress response process. However, limited attention has been given to psychosocial processes involved in the stress response—critical for understanding biological pathways to health—in studies examining racial discrimination as a social determinant of health. We examined whether the superwoman schema (SWS), a multidimensional culture-specific framework characterizing psychosocial responses to stress among AA women, modifies the association between racial discrimination and allostatic load. We used purposive sampling to recruit a community sample of African American women ages 30–50 from five San Francisco Bay Area counties (n = 208). Path analysis was used to test for interactions while accounting for the covariance among SWS subscales using both linear and quadratic models. Significant interactions were observed between racial discrimination and four of the five SWS subscales. Feeling obligated to present an image of strength and an obligation to suppress emotions were each protective whereas feeling an intense motivation to succeed and feeling an obligation to help others exacerbated the health risk associated with experiencing racial discrimination. Our findings affirm the need to consider individual variability in coping and potentially other psychosocial processes involved in the stress response process; and offer several insights that may help elucidate the mechanisms by which racial discrimination gets “under the skin”.